Extrahepatic Textiloma Long Misdiagnosed as Calcified Echinococcal Cyst. (26th February 2013) - Cattaneo, Federico; Graffeo, Massimo; Brunetti, Enrico
Abstract : Textiloma or gossypiboma is a retained surgical swab in the body after an operation and is a complication that can remain undetected for many years and may represent a diagnostic dilemma depending on its location. It may be confused with several focal lesions and an accurate history taking, combined with clinical and instrumental data, is key to suspecting the diagnosis. We report a case of abdominal textiloma that was initially misdiagnosed as echinococcal cyst and discuss the differential diagnosis based on sonographic features and the WHO-IWGE classification.